Atypical Antioxidant Activity of Non-Phenolic Amino-Coumarins - Ureta-Zanartu, M; Aspee-Lamas, A; Cardenas-Jiron, G; Zúñiga-Núñez, D; Barrías-González, P (Royal Society of Chemistry, 2018)
Coumarin compounds have been described as anti-inflammatories, and chemotherapeutic agents as well as antioxidants. However, the origin of the antioxidant activity of non phenolic coumarins remains obscure. In the present report, we demonstrate that non-phenolic 7-dialkyl-aminocoumarins may also have significant antioxidant properties against free radicals derived from 2,2′-azobis(2-amidinopropane) dihydrochloride under aerobic conditions. This atypical behaviour is due to the presence of traces of very reactive hydroxycinnamic acid-type compounds. Changing functional groups at the C-3 and C-4 positions shifts the reactivity of the compounds from peroxyl to alkoxyl free radicals. Kinetic and theoretical studies based on Density Functional Theory support the formation of reactive hydroxycinnamic acid and directly link the antioxidant behaviour of the compounds to hydrogen atom transfer. © The Royal Society of Chemistry 2018.